Differential diagnosis of human Entamoeba infections: Morphological and molecular characterization of new isolates in Argentina - Servian, Andrea (2024)
Entamoeba infections occur worldwide, with higher frequency in countries of low socioeconomic status and poor public health. Since Entamoeba histolytica has long been recognized as the only pathogenic species, making a differential diagnosis of other morphologically identical Entamoeba is important. This study aimed to determine the prevalence of Entamoeba species in two populations from Argentina, make a differential diagnosis by PCR and characterize Entamoeba isolates at the SSU rRNA gene. A total of 493 serial fecal samples were obtained from individuals in the provinces of Buenos Aires (n = 210) and Misiones (n = 283). Samples were examined by conventional methods (formalin---ethyl acetate and Willis flotation) and specific PCRs to differentiate Entamoeba species. Entamoeba isolates were characterized by sequencing a fragment of the SSU rRNA gene. The overall prevalence of Entamoeba infection was 12.4%, being more prevalent in Buenos Aires than in Misiones (14.8% vs. 10.6%). A case of E. histolytica confirmed by PCR and sequence analysis was reported for the first time in Buenos Aires. Moreover, new genetic data on Entamoeba coli and Entamoeba dispar were recorded. The phylogenetic analysis revealed a congruence between morphological characteristics and SSU rRNA gene sequences. This study increases the amount of information on the distribution of these species in Argentina and the region of the Americas.